Molecular Detection Method Developed to Track the Koinobiont Larval Parasitoid Apanteles opuntiarum (Hymenoptera: Braconidae) Imported from Argentina to Control Cactoblastis cactorum (Lepidoptera: Pyralidae) - Srivastava, Mrittunjai (2019)
Apanteles opuntiarum Martínez & Berta (Hymenoptera: Braconidae) is a native natural enemy of the cactus moth, Cactoblastis cactorum Berg (Lepidoptera: Pyralidae) in Argentina, where the 2 species are believed to have co-evolved. Cactoblastis cactorum is an established invasive pest in the US that is rapidly spreading throughout the southeast. Apanteles opuntiarum was imported from Argentina, and reared at the Division of Plant Industry containment facility in Gainesville, Florida, for study as a possible biocontrol agent for release in the US to control C. cactorum. A DNA barcode was developed to enable the identification of the reared parasitoid population. The mitochondrial cytochrome oxidase I (COI) gene of the A. opuntiarum reared in Florida containment was found to be identical to its Argentine founders, but distinctly different from the COI sequences of all other reported Apanteles species in the NCBI (National Center for Biotechnology Information) GenBank. Additionally, the AoF1 and AoR1 primer pair developed in this study specifically amplified the COI gene of A. opuntiarum, but did not amplify the COI gene of the host C. cactorum. Therefore, the COI gene fragment identified in this study has the potential to be used as a DNA barcode specific to A. opuntiarum that can aid in tracking and identifying this parasitoid inside hosts.